Witchcraft and Inquisition in Early Modern Venice. - Seitz, Jonathan (Cambridge University Press, 2011)
Records of the sixteenth- and seventeenth-century witchcraft trials in Venice uncover individuals' conception of the supernatural in early modern Europe.